Characterization of Quadratic Aggregation Functions - Santi Tasena (2019)
IEEE In this work, we show that quadratic aggregation functions on the unit interval-valued lists can be characterized by a set of linear inequalities. We also use these inequalities to find all extreme points of the set of quadratic aggregation functions. Special cases of aggregation functions such as idempotent, conjunction, and disjunction are also considered.